Diurnal and nocturnal measurements of PAH, nitro-PAH, and oxy-PAH compounds in atmospheric particulate matter of a sugar cane burning region - Souza, Kely F.; Carvalho, Lilian R. F.; Allen, Andrew G. [UNESP]; Cardoso, Arnaldo Alves [UNESP] (Elsevier B.V., 2014)
Polycyclic aromatic hydrocarbons (PAHs), nitro-PAHs, and oxy-PAHs were studied in the atmospheric particulate matter of a subtropical rural region (Sao Paulo State, Brazil) affected by emissions from sugar cane burning. Diurnal and nocturnal samples were collected from May to June of 2010. In general, average PAH concentrations were significantly higher at night, suggesting that the compounds were predominantly emitted to the atmosphere during biomass burning (which was mainly performed at night). The maximum average PAH concentration was found for benzo[b]fluoranthene at night (2.9 +/- 5.4 ng m(-3)). Among the nitro-PAH compounds, the highest average concentrations were obtained for 9-nitrophenanthrene in diurnal and nocturnal samples (1.5 +/- 1.2 and 13 +/- 2.1 ng m(-3), respectively). In contrast to the PAH and nitro-PAH compounds, the oxy-PAHs could not be directly associated with sugar cane burning. The most abundant oxy-PAH compound was benzanthrone (1.6 +/- 13 ng m(-3)) at night, followed by 9,10-anthraquinone (1.1 +/- 0.9 ng m(-3)) and 9-fluorenone (0.4 +/- 0.1 ng m(-3)) during the day.A correlation matrix was used to explore the origins of the different compounds. The data suggested that during the daytime, direct emissions (mainly in vehicle exhaust) contributed to the presence of PAHs, nitro-PAHs, and oxy-PAHs in air. Photochemical production also appeared to be a source of the majority of nitro-PAHs and oxy-PAHs, while photolysis could have contributed to removal of the nitro-PAHs during the daytime. At night, sugar cane burning emissions were the primary source of the PAHs and nitro-PAHs, with additional sources also contributing to the levels of oxy-PAHs in the atmosphere. (C) 213 Elsevier Ltd. All rights reserved.
Keywords: Sugar cane burning; Atmospheric particulate matter; PAHs; Nitro; and oxy-PAHs; Brazil